Reactivity Controlled Compression Ignition for clean and efficient ship propulsion - Mikulski, Maciej; Ramesh, Sudarshan; Bekdemir, Cemil (Elsevier, 2019)
Reactivity Controlled Compression Ignition (RCCI) is commonly mentioned as a potential efficient and clean combustion concept. This study makes the first evaluation of natural gas-diesel RCCI combustion for mid-speed marine engines. A state-of-the-art dual-fuel engine with 350 mm bore diameter is the basis for numerical simulations. GT-Power is used to create a one-dimensional air-path model. RCCI is simulated using TNO’s multi-zone combustion model incorporating detailed chemical kinetics. The simulations aim to optimize engine efficiency, with peak incylinder pressure and emissions as constraints. The study shows best-point Indicated Efficiency of 47.8% is achievable (@75% load) using RCCI mode on stock engine hardware, while meeting IMO Tier III’s NOx limit. This performance is similar to the best contemporary marine gas engines, but RCCI also provides additional methane and CO emission reductions. Thus, RCCI combustion can meet Europe’s new rigorous Stage V limits, offering significant improvements in a marine engine’s GHG footprint. Crucially, the study indicates an engine using hardware optimized for RCCI could deliver outstanding indicated efficiencies of 52%, with emissions of below 1g/kWh for all legislative species. This combination of high efficiency and ultra-low emissions would make RCCI combustion an attractive proposition for future marine propulsion and gen-set applications.
Keywords: RCCI; mid-speed engine; marine; natural gas; simulation; energy optimization; fi=Energiatekniikka|en=Energy Technology|